Oral hygiene practices, parents' education level and dental caries pattern in 0 to 5 years-old children - Suzely Adas Saliba Moimaz; Ronald Jefferson Martins; Franklin Delano Soares Forte; Nemre Adas Saliba (Universidade Estadual de Campinas, 2015)
Understanding that dental caries has multifactorial aspects, we attempted to verify the influence of food habits, oral hygiene practices, and parents' education level in the occurrence of this disease in children. One-hundred-thirty children, aged 0 to 60 months, both male and female, were examined in the municipality of Bilac- São Paulo- Brazil. The examination was carried out on the day of National Multivaccination Campaign, using the DMFT index, with the codes and criteria established by WHO. A questionnaire with open and closed questions about children's food and hygiene habits and parents'/ tutors' level of education was applied to parents/tutors. The data were processed using Epi-Info 6.04 software, having been considered significant at p<0.05. It was verified that 83% of the children were bottle fed at night. Of these, 79.6% had the contents of the bottle added with sugar, and this factor was associated with dental caries (p=0.01; OR=1.2; CI=0.2 - 2.3). Oral hygiene had been started before one year of age in 54.6% of the children, and it was carried out twice a day in 46.1% of the cases. Regarding the education level of parents, 51.5% of the mothers and 53.8% of the fathers had more than eight years of education. There was no relationship between the parents' level of education and the presence of dental caries.